Total synthesis of astrosterioside A, an anti-inflammatory asterosaponin1. Issue 72 (18th September 2015) - Dai, Yuanwei; Yu, Biao
<x xml:space="preserve">Abstract</x> An anti-inflammatory starfish saponin was synthesized in a convergent linear sequence of 24 steps and 6.8% overall yield.